Exploring students’ perception of using online learning resources for learning English at SMAN 5 Solok Selatan - Zahra, Firanti; Hanifa, Rizaldy (Journal of English Language Teaching, 2025)
This study aimed to explore students' perceptions of using online learning resources in English language lessons at the twelfth grade of SMAN 5 Solok Selatan. The focus of this research includes three main aspects: cognitive, affective, and conative. The sample consists of 34 twelfth-grade F2 students, who were selected for the sample. The descriptive approach was combined with the quantitative method. Data were collected through a questionnaire containing 23 statements, comprising 11 questions for the cognitive aspect, 9 for the affective aspect, and 3 for the conative aspect. The research findings indicate that students' overall perception of online learning resources is very positive. The cognitive aspect received a mean score of 3.42, the affective aspect 3.47, and the conative aspect 3.40. The students have a positive perception of the benefits, ease of access, and clarity of using online learning resources to support English language learning. Additionally, students also demonstrate a positive attitude, enthusiasm, and a high interest in using them. In terms of conative aspects, students are motivated to independently utilise online learning resources as a means to deepen their understanding of the language. Therefore, their perceived the use of online learning resources has contributed positively to increasing motivation and independence in learning.